Enigmatic doubly scattered tube waves at a crosswell seismic survey. Issue 1 (30th November 2022) - Nakata, Nori; Nakata, Rie; Kato, Ayato; Xue, Ziqiu; White, Malcolm C A
SUMMARY: Enigmatically strong tube waves continue to exist long after the direct wave during repeat crosswell-monitoring surveys at the Nagaoka CO2 injection site in Japan. The tube waves, which have linear moveouts with velocities of 1.29 and 1.41 km s −1 at plastic and steel casings, respectively, are generated by double scattering on the shallow side of the wells. We characterize wavefields to confirm that these late coda waves are tube waves that are excited at the source well, propagate upward, then travel to a receiver well as a body wave, and finally propagate downward along the receiver well. Even though these tube waves result from second-order scattering, they have large amplitudes because of the relatively short distance between source and receiver wells. Because these waves propagate along both wells many times, we can extract detailed information of wave propagation by averaging them to increase the signal-to-noise ratio. We first use the tube waves to relocate sources and receivers between multiple monitoring surveys, demonstrating our ability to correct the severe noise caused by location errors that frequently degrades the repeatability of time-lapse surveys. Then, we apply an inversion based on the physics of tube waves to estimate the location and strength of the scatterers and find that they are predominantly located in the shallow segment of the wells, above the sources, and infer that they are related to local fractures and/or wellbore conditions because their locations do not correspond to the well geometry. Lastly, we use the tube waves to accurately estimate subsurface velocities along the wells. The estimation is stable and robust, and the velocities follow the general trend of subsurface structure seen in the well log data. Due to the receiver spacing, tube-wave analysis cannot resolve a thin, high-velocity layer at the CO2 reservoir. By combining tube waves observed during different stages of the monitoring survey, we can estimate the time-lapse changes of the subsurface velocities.